Zinc-binding properties of Junín virus nucleocapsid protein - Tortorici, María Alejandra (2001)
The arenavirus nucleocapsid protein (N) is a highly basic 63 kDa protein with a dual function during the virus life-cycle. First, it is involved in essential steps of genome replication, promoting the synthesis of the full-length antigenomic copy of S RNA, and second it associates with the genomic RNA to form the nucleocapsid. We have expressed the N protein of Junín virus in E. coli and shown that it binds zinc in vitro. This property is in agreement with the presence in the carboxy-terminal region of the N protein of the CX2HX23CX4C sequence, which resembles a classical zinc-finger motif. The specificity for zinc binding was demonstrated by competition with other divalent metal ions. The ability of the predicted motif to bind zinc was established by analysis of a series of N mutants, including truncated variants and amino acid substitutions. In addition, alternative zinc-binding sites were found.